Numerical simulation of thermal performance of radial manifold microchannel heat sink for electronics thermal management - Kahbandeh, Faramarz; Azarifar, Mohammad; Arik, Mehmet; Harris, Daniel K. (Thermal science and engineering progress, 2025)
Thermal management for electronics has continued to experience significant growth due to the rising demands for computing power along with a continuous decline in packaging volumes. Maintaining the electronics temperature within a predetermined limit is crucial since overheating can result in chip failure, performance deterioration, and even operational hazards in extreme circumstances. This study introduces a novel radial manifold microchannel (RMM) heat sink featuring an upper layer of curved, interdigitated channels designed to enhance flow distribution and reduce pressure drop. The single-phase flow and heat transfer behavior of three curved manifold lengths and three nozzle positions were numerically evaluated using DI water. Results show that the curved design improves thermal performance by up to 14.9% in the best-case scenario at higher flow rates. The Thermal Performance Index (TPI) demonstrated increases of 11% and 14% for the longest and shortest channels with right-edge nozzles, respectively. A full conjugate heat transfer analysis further confirmed that the RMM design reduces overall pressure drop by 19.7% compared to traditional manifold microchannel (TMM) heat sinks. •Curved channels replace straight ones in manifold design to enhance heat sink performance.•Thermal performance improves with the new design, regardless of nozzle position.•Central feeder improves overall flow, despite higher pressure drop in each curved manifold.